Sifat-sifat Lentur Papan Partikel Komposit Kulit Kacang Tanah/Epoksi - S Sudarisman; Muhammad Budi Nur Rahman; Awang Darmawan (Prosiding University Research Colloquium, 2018)
Flexural properties, i.e. load-displacement response, flexuralstrength,failure strain and modulus, of peanut shell particle-reinforced epoxycomposites have been investigated. Four different fiber contents, i.e. 0,20, 30 and 40 vol%, have been fabricated by means of press moldtechnique, and two particle sizes of passing through of mesh 11 but notfor mesh 16, and passing through 16 sievers have been utilized.Specimen preparation and testing were carried out in accordance withthe ASTM D1037. Failure modes were evaluated by closely observingrepresentative photo macrographs of randomly selected failedspecimens. The result revealed that the finer the particles, the higherthe flexural strength and flexural modulus. To the contrary, finerparticle size resulted in lower strain to failure. Almost all specimensshow considerably linear lateral force-deflection relations up to closeto failure. Specimens being produced using coarser particles achievedthe highest flexural strength and modulus of 38.69 MPaand 2.141GPa, respectively, at Vf = 20%, while the highest flexural strain tofailure of 2.48 % was achieved atVf = 40%. Specimens being producedusing finer particles achieved the highest lentur strength and strain tofailure of 43.77 MPa and 2.01 %, respectively, at Vf = 30%, while thehighest lenturmodulus of 2.618 GPa was achieved at Vf = 40%. Unlikepure epoxy specimens which underwent brittle fracture along withbroken into pieces, those filled with peanut particles underwent singleplanebrittle fracture.